Electronic Structure Study of the High-pressure Vibrational Spectrum of FeS2 Pyrite - Wright, Kathleen; Blanchard, M.; Alfredsson, M.; Brodholt, J.; Price, G.; Catlow, C. (American Chemical Society, 2005)
Plane-wave density functional calculations are used to investigate the pressure dependence of the geometry and ?-point phonons of FeS2 pyrite up to 150 GPa. The linear response method is employed to calculate the vibrational properties. Raman-active modes are in excellent agreement with the experimental data available up to 50 GPa,1 and we predict the evolution with pressure of the IR-active modes for which no high-pressure spectroscopic data have been reported so far. Over the wide pressure range investigated here, all vibrational frequencies depend nonlinearly on pressure; their pressure dependence is quantified by determining the full set of mode Gru?neisen parameters and their pressure derivatives.